المنهج الدعوي عند بديع الزمان سعيد النورسي - مقدود, زينة (University of eloued جامعة الوادي, 2015)
تتناول ىذه الد ا رسة تسميط الضوء عمى المنيج الدعوي عند بديع الزمان سعيد النورسي- رحمو الله تعالى- وقد قسمت الد ا رسة إلى أربعة فصول، مع مقدمة وخاتمة وكذا فيارس عامة، فالفصل الأول يوضح الخطوات المنيجية المتبعة في ثنايا البحث والفصل الثاني خصصتو لد ا رسة المنيج الدعوي مفيومو وخصائصو، أىميتو ووسائمو، بينما الفصل الثالث فقد تناولت فيو الكلام عن بديع الزمان سعيد النورسي : بيئتو، حياتو وآثاره، كما تطرقت الد ا رسة في الفصل الأخير إلى معالم المنيج النورسي الدعوي.كما تضمنت خاتمة البحث أىم النتائج التي توصمت إلييا من خلال الد ا رسة ليذه الشخصية الدعوية العالمية In this research we talked about the invitatiomal way of Badie Ezzaman Said Ennaoirassi. The study diveded to four parts, wrtl an intrduction and conchision, also a general contants. The first part explains the methodical stepa which followed in this research. The secoud part talks obout the inritation way. Its definition and its characteristic, its inpotauce and its tools. While, the third part ltalk obout the biography of Badie Ezzaman Said Ennaoirassi. In the last part lurite abot the Ennaoirassi method finally in the conclusion lwrite obout the imprtant results which Lconsidered from my study to this personality..
ماستر دعوة
Keywords: المنيج، الدعوة، المنيج الدعوي; The method - The invitation - The invitational method